PROSPECTS FOR THE USE OF INHALATION ANTIBACTERIAL DRUGS IN RESPIRATORY INFECTIONS ( REVIEW) - Shakhboskhon Makhmudovich Ahmedov (Scholar Express Journals, 2023)
The need to find ways to improve the effectiveness of antibacterial therapy is due to the dramatic escalation of resistance to antibacterial drugs (ABD), while the growth rate of resistance to antibacterial drugs is outpacing the dynamics of the development of new drugs. The article presents up-to-date data on existing inhaled ABPs, allowing to evaluate their effectiveness and safety.
Keywords: antibacterial drug resistance; inhalation antibacterial drugs; ower respiratory tract infections; pyocyanic infection